Dampak Pernikahan Dini terhadap Kehamilan Remaja Putri - Tambunan, Yessi Syahradesi Br.; Cane, Purnama Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the impact of early marriage on teenage girls' pregnancy in Darul Amin Village, Lawe Alas District, Southeast Aceh Regency. The research method used is quantitative correlational and uses secondary data using a case-control design. The results of the study indicate that there is a relationship between knowledge and early marriage (pvalue = 0.005, OR value = 0.180), there is a relationship between parental income levels (pvalue = 0.001, OR value = 5.90), there is a relationship between respondent education levels (pvalue = 0.002, OR value = 5.50). Variables that are not related to early marriage are parental trust levels (p-value = 0.806, OR value = 1.45). The conclusion is that there is a relationship between teenage girls' knowledge, parental income, adolescent girls' education, and early marriage, so there is an impact of early marriage on adolescent girls' pregnancy in Darul Amin Village, Lawe Alas District, Southeast Aceh Regency in 2024. Keywords: Pregnancy, Early Marriage, Teenage Girls